Development of Student Worksheets Assisted by Powtoon Media on Elasticity and Hooke's Law to Improve Student Learning Outcomes - Magrib, Yunisa Sy; Supartin; Jahja, Mohammad (Jurnal Pijar Mipa, 2024)
This research is a type of development research (Research and Development). with the aim of knowing the quality (Validity, Practicality, and effectiveness) of student worksheets assisted by Powtoon media on the material Elasticity and Hooke's Law. This research is a type of development research that refers to 4-D Model development research consisting of four development stages, namely Defining, Designing, Developing, and Disseminating. After being validated by 3 validators, a limited trial was carried out by 36 class XI participants at SMA Negeri 1 Kabila. Data collection techniques in this research used expert validation sheets, teacher and student response questionnaires, and student learning outcome tests. The research results show that validation is in the "valid" category. The practicality of students' worksheets assisted by Powtoon media can be seen from the results of the implementation of learning in class, and teachers and students show the category "very well implemented." It can be concluded that the worksheet for students developed with the help of Powtoon media has met the criteria of being valid, practical, and effective so that it is suitable for use in physics learning at school. The difference between this research and research conducted by researchers lies in the media used, the materials used, and the location studied. Another difference is that researchers only use 3 stages in the four-D model, namely define, design, and develop.